Bathyraja albomaculata, Whitedotted Skate - Pollom, R. (2020)
The Whitedotted Skate (Bathryraja albomaculata) is a large (to 150 cm total length) skate that occurs in the Southeast Pacific and Southwest Atlantic Oceans from Coquimbo, Chile south around Cape Horn and north to Uruguay, including the Falkland Islands (Malvinas) and the Burdwood Bank, and is demersal on the inshore continental shelf and upper slope at depths of 55?945 m. It is captured in industrial longline and trawl fisheries, which operate throughout its range. Although discarded dead in some parts of its range, it is utilized for human consumption in others. In the Southeast Pacific, skates targeted in fisheries (Dipturus spp.) have undergone severe population reductions where this species is captured as unmanaged bycatch. In the Southwest Atlantic, there are some general management measures in place for skates but they are not species-specific. This skate is now absent from approximately one-third of its distribution in Argentina due to heavy fishing pressure on skates. Overall, due to the level of exposure to inadequately managed fisheries, noted population reductions in other skates, its lack of refuge at depth, a suspected decline in area of occupancy, and a combination of declines in some areas and stability in others, it is suspected that the Whitedotted Skate has undergone a population reduction of 30-49% over the past three generations (40.5 years). Therefore, the Whitedotted Skate is assessed as Vulnerable A2bd.